Higher education and democracy : essays on service-learning and civic engagement - Saltmarsh, John A., 1957-; Zlotkowski, Edward A., 1944- (Temple University Press, 2011)
Higher Education and Democracy is a collection of essays written over the last ten years on how civic engagement in higher education works to achieve what authors John Saltmarsh and Edward Zlotkowsi consider to be the academic and civic purposes of higher education. These include creating new modes of teaching and learning, fostering participation in American democracy, the development and respect for community and civic institutions, and encouraging the constant renewal all of these dimensions of American life.